SLIT2/ROBO1-miR-218-1-RET/PLAG1: a new disease pathway involved in Hirschsprung's disease - Tang, Weibing (J Cell Mol Med, 2015)
Hirschsprung's disease (HSCR) is a rare congenital disease caused by impaired proliferation and migration of neural crest cells. We investigated changes in expression of microRNAs (miRNAs) and the genes they regulate in tissues of patients with HSCR. Quantitative real-time PCR and immunoblot analyses were used to measure levels of miRNA, mRNAs, and proteins in colon tissues from 69 patients with HSCR and 49 individuals without HSCR (controls). Direct interactions between miRNAs and specific mRNAs were indentified in vitro, while the function role of miR-218-1 was investigated by using miR-218 transgenic mice. An increased level of miR-218-1 correlated with increased levels of SLIT2 and decreased levels of RET and PLAG1mRNA and protein. The reductions in RET and PLAG1 by miR-218-1 reduced proliferation and migration of SH-SY5Y cells. Overexpression of the secreted form of SLIT2 inhibited cell migration via binding to its receptor ROBO1. Bowel tissues from miR-218-1 transgenic mice had nerve fibre hyperplasia and reduced numbers of gangliocytes, compared with wild-type mice. Altered miR-218-1 regulation of SLIT2, RET and PLAG1 might be involved in the pathogenesis of HSCR.